PEMBERIAN KOMBINASI VITAMIN B1, B6 DAN B12 SEBAGAI FAKTOR DETERMINAN PENURUNAN NILAI TOTAL GEJALA PADA PASIEN NEUROPATI PERIFER DIABETIK - Ratna Sari Kusuma Dewi; Rizaldy Taslim Pinzon; Sapto Priatmo (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2016)
Diabetic neuropathy is defined as symptoms of peripheral nerve dysfunction in people with diabetes after the exclusion of other causes. According to the earlier studies symptoms of neuropathy such as pain, burning, paresthesia/tingling and numbness can be reduced with neurotropic supplementation. The aim of the research is to determine vitamin B1, B6 and B12 as a determinant factor in the reduce total symptom score in patient with diabetic peripheral neuropathy. This research used case series studies and choose 43 sample with consecutive sampling method. We observed symptoms of diabetic peripheral neuropathy (pain, burning, tingling and numbness) measured as total symptoms score, among the patients treated with vitamin B1 (100mg), B6 (100mg) and B12 (5000mcg) for a month. Measurement of total symptoms score performed at first meeting, the second week later (day-14) and the fourth week later (day-30). The data were analyzed using univariate and bivariate statistics. The patients (n=43) consisted of 20 male (46.5 %) and 23 female (53.5 %). The symptoms of diabetic peripheral neuropathy (pain, burning, tingling and numbness) that measured by total symptoms score compared with first visit (4.70 1.83), second visit (2.99 1.61) and third (2:37 1.62). Bivariate analysis, showed a correlation between a reduction in total symptoms score after giving therapy of vitamin B1 (100mg), B6 (100mg) and B12 (5000mcg) with p = 0.00. Vitamin B1, B6 and B12 proved to be a determinant factor to reduce total symptoms score (pain, burning, tingling, and numbness) in patients with diabetic peripheral neuropathy.